Effective control mechanisms of research on climate engineering techniques for the public good—The London Protocol regulatory approach as a role model - Ginzky, Harald; Oschlies, Andreas (Frontiers in Climate, 2024)
Climate engineering, including Carbon Dioxide Removal and Solar Radiation Modification techniques, increasingly gets into the public discussion on effective climate change policies. As most of these techniques are still in their infancy, the critical question arises whether and how in situ research and development should be controlled and governed by competent governmental authorities. In this context, public funding may serve as a pivotal factor alongside appropriate regulatory approaches and may itself also be regulated by legal mechanisms. We here argue that the London Protocol, that includes regulation of research into marine geoengineering, is a promising role model also for regulating other climate engineering approaches, including -if ever appropriate- solar radiation modification techniques. We propose to consider the London Protocol as a role model for governance schemes to be developed for emerging research and possible deployment efforts regarding climate engineering.